Measuring Social Media Addiction among University Students - Aslan, İmran and YAŞAR, Mehmet Emin (International Journal of Contemporary Economics and Administrative Sciences, 2020)
New developments in technology have changed the habits of people and people can find the things of real life in virtual worlds. Interacting in online platforms and sharing options of social media have made the life of students more easy while Social Media Addiction becomes a problem among young people, causing to mental and physical problems in long run by using in an excessive manner. The aim of this study is to determine the usage purposes and addiction level of social media among university students according to age, gender, usage years and daily usage. For that aim, 665 students were surveyed in an online platform at Bingöl University in 2019. Descriptive statistics, Kruskal Wallis Test, One-Way ANOVA test, Factor Analysis and Correlation Analysis statistical methods are used to analyze data by SPSS 20 software. Instagram, youtube and facebook were found to be three mostly used social media networks respectively. Maintaining communication with existing friends, listening music and sharing things are main usage purposes for females while males prefer social media for following a group, playing games and meeting new people. According to gender, there are significant differences just for conflict factor that males spend more time on social media than doing their daily responsibilities and activities supported with high correlation between gender and conflict factor that males are more addictive. Moreover, younger university students have higher conflict addiction and as students use social media more in years and higher daily hours, they become more addictive in general. Students spend daily most of their social media time for communicating with existing friends and chatting. Daily usage has the strongest correlation with occupation factor. Furthermore, the strongest correlation is seen between relapse and conflict factors and the most effective factor on Social Media Addiction Scale (SMAS) is conflict factor.